TEACHERS' UNDERSTANDING OF DEEP LEARNING IN THE INTEGRATION OF MORAL MESSAGES IN MATHEMATICS LEARNING - Fitri Oktafiyana; Nafisa Nurfatin; Sofyan Iskandar (SOSIOEDUKASI, 2026)
This study aims to describe the extent to which teachers understand the concept of deep learning in the integration of moral messages in mathematics learning at SDN 221 Babakan Sentral. The research background is based on the demands of 21st century education which emphasizes that teachers not only pursue academic achievements, but also the development of students' character and moral values. The deep learning approach is considered relevant because it emphasizes meaningful understanding, reflection processes, and the relationship between knowledge and life values. The research used a qualitative case study method with the subjects of a grade VI teacher, the principal, and two students. Data were obtained through in-depth interviews, participatory observations, and document studies, then analyzed through reduction, data presentation, and conclusion drawing of the Miles and Huberman models. The findings show that teachers' understanding of deep learning is still limited to conceptual and cognitive aspects, not yet touching the reflective and moral dimensions. Teachers begin to integrate the values of honesty, responsibility, and cooperation, but have not optimally formed students' ethical awareness. The research concludes the need to improve pedagogical competence and reflective awareness through value-based training and a collaborative culture of schools.